Crystal structure of glutamate-1-semialdehyde-2,1-aminomutase from Arabidopsis thaliana - Song, Yingxian (International Union of Crystallography, 2016)

(untitled) (Acta Crystallogr F Struct Biol Commun)
Glutamate-1-semialdehyde-2,1-aminomutase (GSAM) catalyzes the isomerization of glutamate-1-semialdehyde (GSA) to 5-aminolevulinate (ALA) and is distributed in archaea, most bacteria and plants. Although structures of GSAM from archaea and bacteria have been resolved, a GSAM structure from a higher plant is not available, preventing further structure–function analysis. Here, the structure of GSAM from Arabidopsis thaliana (AtGSA1) obtained by X-ray crystallography is reported at 1.25 Å resolution. AtGSA1 forms an asymmetric dimer and displays asymmetry in cofactor binding as well as in the gating-loop orientation, which is consistent with previously reported Synechococcus GSAM structures. While one monomer binds PMP with the gating loop fixed in the open state, the other monomer binds either PMP or PLP and the gating loop is ready to close. The data also reveal the mobility of residues Gly163, Ser164 and Gly165, which are important for reorientation of the gating loop. Furthermore, the asymmetry of the AtGSA1 structure supports the previously proposed negative cooperativity between monomers of GSAM.